2004
DOI: 10.1074/jbc.m402260200
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic NADP+-dependent Isocitrate Dehydrogenase Plays a Key Role in Lipid Metabolism

Abstract: NADPH is an essential cofactor for many enzymatic reactions including glutathione metabolism and fat and cholesterol biosynthesis. We have reported recently an important role for mitochondrial NADP ؉ -dependent isocitrate dehydrogenase in cellular defense against oxidative damage by providing NADPH needed for the regeneration of reduced glutathione. However, the role of cytosolic NADP ؉ -dependent isocitrate dehydrogenase (IDPc) is still unclear. We report here for the first time that IDPc plays a critical rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
164
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(172 citation statements)
references
References 32 publications
3
164
1
1
Order By: Relevance
“…Thus, the CAC enzyme is unlikely to be involved in lipogenesis from glutamine. Likewise, in rapidly growing cells the need for cytosolic NADPH for biosynthesis will favor flux of the cytosolic NADP-dependent enzyme toward ␣-ketoglutarate as shown recently in 3T3-L1 cells (10). This study also found that overexpression of cytosolic NADP-dependent enzyme in mice leads to increased lipogenesis in liver and fat, consistent with a reaction producing cytoso-lic NADPH.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Thus, the CAC enzyme is unlikely to be involved in lipogenesis from glutamine. Likewise, in rapidly growing cells the need for cytosolic NADPH for biosynthesis will favor flux of the cytosolic NADP-dependent enzyme toward ␣-ketoglutarate as shown recently in 3T3-L1 cells (10). This study also found that overexpression of cytosolic NADP-dependent enzyme in mice leads to increased lipogenesis in liver and fat, consistent with a reaction producing cytoso-lic NADPH.…”
supporting
confidence: 68%
“…An alternative to glutaminolysis is the reductive carboxylation pathway where glutamine enters the CAC as ␣-ketoglutarate and is converted to citrate via isocitrate dehydrogenase (IDH) operating in reverse of the CAC direction. Evidence for reductive carboxylation in transformed cells is the finding that [5][6][7][8][9][10][11][12][13][14] C]glutamine labels acetyl-CoA-derived carbons of lipids (6,7). Additionally, reversal of IDH has been detected in perfused liver and heart as evidenced by the mass isotopomer distribution (MID) of [ 13 C]citrate following perfusion with [ 13 C]glutamine (8,9).…”
mentioning
confidence: 99%
“…Amino acids can be used for lipogenesis in adipose tissues, which might explain why these tissues need high levels of cytosolic IDH1 and why overexpression of IDH1 promotes lipogenesis in adipose tissues and livers of IDH1 transgenic mice (7). In contrast, in skeletal muscle and heart where cytosolic IDH1 is absent or very low, the mitochondrial α-KG is S4C.…”
Section: Discussionmentioning
confidence: 98%
“…It was recently reported that IDH1 protects murine hepatocytes from endotoxin-induced oxidative stress by regulating the intracellular NADP + /NADPH ratio (12). Because NADPH is a major cofactor for fatty acid biosynthesis, IDH1 transgenic mice showed markedly higher liver and serum levels of total TG and cholesterol compared with WT mice, suggesting that IDH1 might be a major NADPH producer for lipid biosynthesis (7). Others have found that IDH1 mediates reductive glutamine metabolism for lipogenesis in hypoxic cells (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation